The Role of Primary Care Physicians (DLP) in Community Care - Dhanasari Vidiawati Trisna Sanyoto; Nur Afrainin Syah (Faculty of Medicine, Public Health, and Nursing, 2018)
Dokter Layanan Primer (DLP) or Primary Care Physician (PCP) is a newly introduced term by the Indonesian government in 2013 since the enforcement of Medical Education Law 20/2013. DLP is a physician who solidifies his/ her education and career in primary care. They have postgraduate medical training in primary care and are experts in this field. In most countries, to be a generalist physician practising at primary care facilities such as health centres and primary care clinics, medical school graduates have to take postgraduate medical training to be proficient in terms of knowledge and skills in primary care services. Family medicine is the main body of knowledge of the primary care postgraduate training program in those countries even though their graduates are called differently among countries. These physicians are called family doctors or family physicians in the United States of America (USA), general practitioners (GPs) in Commonwealth countries, huisarts in the Netherlands. In Indonesia, where social, economic, and cultural diversity is very high in various regions, in addition to Family Medicine, Community Medicine and Public Health....